1998
DOI: 10.1080/00222899809601324
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Prehension: The Influence of Task Goals

Abstract: A single study is reported in which the influence of age and task goal on reaching and grasping movements were examined. Ten young and 10 elderly subjects reached and grasped a disk (4.5-cm diameter) and then either (a) placed it in a well, (b) placed It in a box, or (c) threw it in a box, all located 30 cm to the left of the disk. The reach-to-grasp movements were analyzed over two phases: the approach to capture the disk and the transporting of the disk. Differential effects were observed over the two phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
18
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
7
18
2
Order By: Relevance
“…Similar findings have been observed in the healthy elderly (Weir, MacDonald, Mallat, Leavitt, & Roy, 1998) and to some extent in healthy 10.5‐month‐old infants (Claxton, Keen, & McCarty, 2003). Active healthy elderly slowed the approach phase of their reaching for the object and spent a longer duration in deceleration while completing the fitting task, compared with the throwing task.…”
supporting
confidence: 86%
“…Similar findings have been observed in the healthy elderly (Weir, MacDonald, Mallat, Leavitt, & Roy, 1998) and to some extent in healthy 10.5‐month‐old infants (Claxton, Keen, & McCarty, 2003). Active healthy elderly slowed the approach phase of their reaching for the object and spent a longer duration in deceleration while completing the fitting task, compared with the throwing task.…”
supporting
confidence: 86%
“…When healthy adults were asked to grasp a disk (4 cm in diameter) and then to either fit it into a small well (4.1 cm in diameter) or throw it inside a box (20 cm × 40 cm × 15 cm), the reaches they used to approach the disk during the fitting task were slower, with a longer duration and a longer time spent in the deceleration phase, than were the reaches in the throwing task (Marteniuk et al). Similar findings have been observed in the healthy elderly (Weir et al, 1998) and to some extent in healthy 10.5-month-old infants (Claxton et al). Active, healthy elderly people slowed the approach phase of their reaching and spent a longer duration in deceleration while completing the placing task (i.e., the fitting task), as compared with their performance in the throwing task.…”
supporting
confidence: 89%
“…Factors from the actor, the environment, and the task affect reaching patterns (Newell). In previous studies, researchers have demonstrated that what adults are going to do with an object immediately after picking it up affects the reaching pattern used to approach the object (Claxton, Keen, & McCarty, 2003;Gentilucci, Castiello, Corradini, & Scarpa, 1991;Johnson-Frey, McCarty, & Keen, 2004;Marteniuk, MacKenzie, Jeannerod, Athenes, & Dugas, 1987;Weir, MacDonald, Mallat, Leavitt, & Roy, 1998;Weir, MacKenzie, Marteniuk, & Cargoe, 1991). When healthy adults were asked to grasp a disk (4 cm in diameter) and then to either fit it into a small well (4.1 cm in diameter) or throw it inside a box (20 cm × 40 cm × 15 cm), the reaches they used to approach the disk during the fitting task were slower, with a longer duration and a longer time spent in the deceleration phase, than were the reaches in the throwing task (Marteniuk et al).…”
mentioning
confidence: 99%
“…The toss action was assumed a simple task, while the place task was assumed a more complex task, based on the amount of motor precision required to perform the task. The tasks were chosen as previous work (Weir, MacDonald, Mallat, Leavitt, & Roy, 1998) had found, using placing and throwing tasks, that the precision required to perform the task influenced the duration of movement and the relative timing of arm deceleration.…”
Section: Apparatusmentioning
confidence: 99%